Preterit expansion and perfect demise in Porteño Spanish and beyond : a critical perspective on cognitive grammaticalization theory - Fløgstad, Guro, 1981- (Brill's studies in historical linguistics ;, 2016)
In Preterit Expansion and Perfect Demise in Porteño Spanish and Beyond, Guro Nore Fløgstad offers an original account of the way in which the Preterit category has expanded, at the expense of the Perfect, in Porteño Spanish - a variety spoken in Buenos Aires, Argentina. Through primary sources and a large cross-linguistic sample, Fløgstad convincingly shows that the expansion of a Preterit is not rare in the languages of the world. This finding challenges the prevailing view in historical morphosyntax, and especially in usage-based grammaticalization theory, namely the alleged preference for analytic over synthetic forms, and the possibility of prediction based on the source meaning in grammaticalization. This book is fully available in Open Access.